2019
DOI: 10.1101/643577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of APOE genotype and streamline density volume, on hippocampal CA1 down-regulation: a real-time fMRI virtual reality neurofeedback study

Abstract: † The complete list of collaborators of the ALFA Study can be found in the acknowledgements section *Correspondence to: jlmolinuevo@barcelonabeta.org Highlights • APOE-ε4 alleles impact hippocampal down-regulation neurofeedback performance.• Hippocampal streamline density volume is associated with decreased hippocampal down-regulation performance.• Bilaterally cohesive hippocampal activity is associated with better memory performance.• We provide a novel paradigm to investigate self-regulation and brain functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Further possible candidates for predicting neurofeedback success might be factors that have already been identified to be predictive of cognitive and behavioral training success in non‐neurofeedback studies, for example, activity in areas related to stimulus encoding and motor control has been found to be predictive of motor learning (Herholz, Coffey, Pantev, & Zatorre, 2016), and activity in the motor network has been found to predict training‐related changes in working memory (Simmonite & Polk, 2019). Finally, very recent work by Skouras et al indicates that neurofeedback learning performance can be influenced by biological factors such as genetic and anatomical predispositions (Skouras et al, 2019), thus demonstrating the complexity of the underlying processes and the need for using multimodal data sets.…”
Section: Discussionmentioning
confidence: 99%
“…Further possible candidates for predicting neurofeedback success might be factors that have already been identified to be predictive of cognitive and behavioral training success in non‐neurofeedback studies, for example, activity in areas related to stimulus encoding and motor control has been found to be predictive of motor learning (Herholz, Coffey, Pantev, & Zatorre, 2016), and activity in the motor network has been found to predict training‐related changes in working memory (Simmonite & Polk, 2019). Finally, very recent work by Skouras et al indicates that neurofeedback learning performance can be influenced by biological factors such as genetic and anatomical predispositions (Skouras et al, 2019), thus demonstrating the complexity of the underlying processes and the need for using multimodal data sets.…”
Section: Discussionmentioning
confidence: 99%
“…In this context we want to highlight the recent research from Skouras et al who found an association between a clinical biomarker for AD and self-regulation success (please note that the study was not included in our systematic review because the authors did not report cognitive or clinical outcome measurements). First, the authors showed that participants carrying APOE-ε4 alleles showed lower selfregulation performance during hippocampal down-regulation compared to non-carriers (Skouras et al, 2019). Second, they reported reduced eigenvector centrality (i.e., less influence based on iterative whole-brain connectomics) in the anterior cingulate cortex and primary motor cortex during hippocampus downregulation when comparing cognitively unimpaired participants who had abnormal levels of CSF amyloid-β peptide 42 with cognitively unimpaired participants with lower CSF amyloidβ peptide 42 levels (Skouras et al, 2020).…”
Section: Comprehensive Clinical Documentationmentioning
confidence: 99%
“…The design of the VR paradigm was guided by the following objectives: a) we used VR to make the task immersive, engaging and entertaining; b) that in turn enabled making the task particularly long, 30 minutes, to maximize 1 st -level statistical power; c) we employed sliding-window closed-loop NF to achieve an optimal design for analysis of functional connectomics; d) we narrowed the NF target ROI to hippocampal subfield CA1, that presents atrophy in AD but not in healthy aging (Frisoni et al, 2008;Wilson et al, 2004;Yushkevich et al, 2015), while also being consistently implicated in memory encoding (Kim, 2011) and differing in activity in patients (Schwindt and Black, 2009). Prior to the acquisition of CSF biomarkers, the task was validated in a larger, partly independent sample (77% overlap), by showing that hippocampal downregulation was associated with genetic predisposition to AD, neurodevelopmental processes and bilateral cohesion of hippocampal function (Skouras et al, 2019b).…”
Section: Vr Paradigm and Real-time Nfmentioning
confidence: 99%